From waste to sustainable production: Experimental design and optimization of sustainable concrete using response surface methodology and life cycle assessment - Ulucan, Muhammed (Elsevier, 2024)
This study focuses on a holistic approach to investigate the engineering properties (microstructural, mechanical, environmental, and economic) of sustainable concretes produced using recycled aggregate and supplementary cementitious material (SCM). Compressive strength tests was conducted on 24 sustainable concrete series for the mechanical properties. Statistical analyses were performed using the response surface methodology, and mathematical models were developed considering the strength values obtained. Developed model-based optimization solutions were applied to determine the mix proportions of the optimization series containing lower cement dosage and SCM with the same hardened concrete properties as the reference concrete series. Considering these mix proportions, life cycle assessments were performed and environmental and economic properties were compared. A comparison of Ref-6 and Opt-6 series reveals that the global warming potential (GWP), energy consumption (EC), and waste generation (WG) values are 422.4-330.9 kg CO2 eq, 1294-1044 MJ, and 1294-1222 kg, respectively. This situation resulted in a reduction of 21.7% in GWP values, 19.3% in EC values, and 5.6% in WG values. Similarly, the economic comparison of these series indicates that the total cost values are 81.9-75.7 , respectively, resulting in 7.7% reduction. Finally, Scanning Electron Microscopy analyses were conducted to examine the microstructural properties. The use of fly ash at 10% improved the microstructure properties and increased the C-S-H gel formation. It is thought that the process of transition from these waste materials to sustainable production is of critical importance, especially in places that are heavily damaged after devastating earthquakes and where large amounts of waste materials are generated.
Keywords: Sustainable development; Circular economy; Life cycle assessment; Response surface method